Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Mass timber wall splice connection using glued-in rods: Design methodology, implementation, and shake-table testing in a six-story building - Steven Kontra; Andre R. Barbosa; Arijit Sinha; Steve Pryor; Reid B. Zimmerman; Barbara Simpson; John W. van de Lindt; Shiling Pei; Gustavo A. Araújo R.; Morgan McBain; Ludovica Pieroni; Prashanna Mishra; et al. (Engineering Structures, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

N-Acetylcysteine Dose and Treatment Duration in High-Risk Acetaminophen Ingestions Treated Within Eight Hours: A Retrospective Cohort Study - C. James Watson; Michael D. Simpson; Nishita Saraiya; Christopher A. Wilkosz; Michael B. Yu; Michele M. Burns; Mark J. Neavyn; Karen E. Simone; Tania D. Strout (Journal of Medical Toxicology, 2026)
Introduction Toxicologists may use high dose n-acetylcysteine (HD-NAC) for early-treated high-risk acetaminophen ingestions (EHRAI) given concerns over standard NAC (S-NAC) dosing’s efficacy. We utilize the novel, clinically relevant outcome of mean additional 16-hour NAC maintenance infusions (NMI) to evaluate differences in treatment duration for EHRAI patients treated with S-NAC versus HD-NAC. Methods Retrospective multistate poison center study from 1/1/2019-7/4/2024 of patients ≥ 13-years-old who were treated with S-NAC or HD-NAC within eight hours of a high-risk acetaminophen ingestion. The primary outcome was mean additional NMI. Secondary outcomes were NAC infusion duration, hepatotoxicity, coagulopathy, transplant, and death. Sensitivity analyses evaluated for robustness of findings. Results Of 127 included cases, 52.0% (66/127) received HD-NAC. 7.1% (9/127) had anti-peristaltic co-ingestions. HD-NAC cases received more fomepizole (23.1% versus 1.6%; difference 21.1%). Acetaminophen concentrations controlled for time since ingestion were similar (mean acetaminophen ratio for HD-NAC: 2.7, IQR: 2.3, 3.3 versus S-NAC: 2.4, IQR: 2.2, 2.7; difference − 0.3). 26.0% (33/127) received NMI solely for residual detectable serum acetaminophen. There was no difference in mean additional NMI (HD-NAC: 0.53 versus S-NAC: 0.38; p = 0.240). Median NAC infusion durations were equal across groups (21.0; IQR: 21.0, 37.0; difference 0.0) ( p = 0.137). One patient per group developed hepatotoxicity; there were no transplants or deaths. Sensitivity analyses yielded similar results. Conclusions We found no difference in mean NMI for EHRAI based on NAC dose. These findings support additional NMI as an objective, common, clinically relevant outcome for acetaminophen toxicity research.

The Separate Roles of Vascular Plants and Sphagnum Mosses in Regulating the Net CO 2 Exchange in a Boreal Peatland During Key Phenological Phases - Antonia Hartmann; Kyohsuke Hikino; Lukas Guth; Gillian Simpson; Järvi Järveoja; Mats B. Nilsson; Matthias Peichl (Global Change Biology, 2026)
Boreal peatlands provide an important carbon store, which is highly susceptible to future changes in the global climate. Predictions of climate feedbacks on the peatland carbon balance require an in‐depth understanding of how vegetation dynamics and environmental conditions jointly govern the production and decomposition of organic matter. However, detailed knowledge on the separate roles of plant functional groups (PFGs) in regulating peatland production and respiration fluxes in response to various abiotic factors at sub‐seasonal scales is currently lacking. In this study, we used high‐temporal resolution CO 2 flux data from an automated chamber system established across experimental vegetation removal plots to separate the production and respiration fluxes of vascular plants and Sphagnum mosses over three growing seasons (2021–2023) in a boreal peatland. We found that gross primary production (GPP) of Sphagnum mosses exceeded that of vascular plants during green‐up (average ratio: 1.18) and senescence (1.11), whereas vascular plants were the main contributor during the peak season (0.88). Vascular plants dominated autotrophic respiration (RA; 78%–93%) in all phenophases and contributed 38%–40% to growing season ecosystem respiration. For both PFGs, plant phenology was the primary driver for variations in GPP during green‐up, whereas photosynthetic photon flux density was most important in regulating GPP during the peak season and senescence. Vascular plants reached greater maximum GPP throughout all phenophases, whereas Sphagnum mosses had a higher initial light use efficiency during green‐up and senescence. Moss RA exhibited greater daytime temperature sensitivity than vascular plants during the peak season and senescence, but not during nighttime. These findings highlight that climate change effects on vegetation phenology and composition may strongly alter the peatland carbon cycle. Thus, understanding the separate roles of vascular plants and Sphagnum mosses in regulating production and respiration fluxes in different environmental conditions is crucial to improve predictions of northern peatland carbon cycle‐climate feedbacks.

Otolith-based age and growth of the spotted moray eel (Gymnothorax moringa) and squirrelfish (Holocentrus adscensionis) from Ascension Island and St Helena - Valerio Visconti; Elizabeth D. L. Trip; Ian Woodgate; Tiffany Simpson; James B. Bell; Paul Whomersley; Leeann Henry; Kirsty Jones; Kyne Krusic-Golub; Simon Robertson; Serena Wright (Frontiers in Marine Science, 2025)
This study investigates the age-based life-history traits of two groundfish species, the spotted moray eel ( Gymnothorax moringa ) and squirrelfish ( Holocentrus adscensionis ), found in Ascension Island and St Helena. Both islands are part of the UK Overseas Territories (UKOTs) and are known for their fish biodiversity. The research aims to provide essential life-history information to support sustainable management of these species within the Marine Protected Areas (MPAs) of Ascension Island and St Helena. A total of 556 fish samples were collected between 2014 and 2021, with 279 individuals of G. moringa and 277 individuals of H. adscensionis . We found significant differences in life span, adult body size, and growth rates between the two islands for both species. G. moringa exhibited longer life spans (32 vs 29 years) and faster growth rates at Ascension Island compared to St Helena, while H. adscensionis showed larger adult sizes at Ascension Island but shorter life spans (21 vs 27 years) compared to St Helena. The study highlights the importance of developing locality-specific species life history data collections to monitor population dynamics in MPA areas. This biological information is essential to allow future assessment programs on the potential impacts of climate change and inshore human activities, including the impacts of inshore fisheries. Future research should focus on reproductive biology, size and age at maturity, and migration patterns to enhance the accuracy of sustainability assessments for these fisheries.

Origin and HFSE enrichment potential of a Late Cretaceous basalt to peralkaline rhyolite suite in central Queensland, Australia - D. Purdy; B. Simpson; N. Kositcin; J. Fitzherbert; H. Dalton (Australian Journal of Earth Sciences, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Variations in Ecosystem‐Scale Methane Fluxes Across a Boreal Mire Complex Assessed by a Network of Flux Towers - Koffi Dodji Noumonvi; Mats B. Nilsson; Joshua L. Ratcliffe; Mats G. Öquist; Natascha Kljun; Johan E. S. Fransson; Järvi Järveoja; Anders Lindroth; Gillian Simpson; Jacob Smeds; Matthias Peichl (Global Change Biology, 2025)
High latitude mires are key ecosystems in the context of climate change since they store large amounts of carbon while constituting an important natural source of methane (CH 4 ). However, while a growing number of studies have investigated methane fluxes (FCH 4 ) at the plot‐ (~1 m 2 ) and ecosystem‐scale (~0.1–0.5 km 2 ) across the boreal biome, variations of FCH 4 magnitudes and drivers at the mesoscale (i.e., 0.5–20 km 2 ) of a mire complex are poorly understood. This study leveraged a network of four eddy‐covariance flux towers to explore the spatio‐temporal variations in ecosystem‐scale FCH 4 across a boreal mire complex in northern Sweden over 3 years (2020–2022). We found a consistent hierarchy of drivers for the temporal variability in FCH 4 across the mire complex, with gross primary production and soil temperature jointly emerging as primary controls, whereas water table depth had no independent effect. In contrast, peat physical and chemical properties, particularly bulk density and C:N ratio, were identified as significant baseline constraints for the spatial variations in FCH 4 across the mire complex. Our observations further revealed that the 3‐year mean annual FCH 4 across the mire complex ranged from 7 g C m −2 y −1 to 11 g C m −2 y −1 , with a coefficient of variation of 16% that is similar to the variation observed among geographically distant mire systems and peatland types across the boreal biome. Thus, our findings highlight an additional source of uncertainty when scaling information from single‐site studies to the mire complex scale and beyond. Furthermore, they suggest an urgent need for peatland ecosystem models to resolve the mesoscale variations in FCH 4 at the mire complex level to reduce uncertainties in the predictions of peatland carbon cycle‐climate feedbacks.

CSF Markers of TG6 Autoimmunity in Gluten Ataxia - Mara-Luciana Floare; Stephen B. Wharton; Julie E. Simpson; Daniel Aeschlimann; Marios Hadjivassiliou (The Cerebellum, 2025)
Gluten ataxia (GA) is the primary neurological manifestation of gluten sensitivity, characterised by loss of Purkinje cells throughout the cerebellar cortex and rooted in autoimmunity to transglutaminase 6 (TG6). Previous studies have shown the contribution of serum anti-TG6 antibodies to disease progression; however, it remains unclear where these antibodies are produced and how they gain access into the brain parenchyma. This study aims to provide an immunological assessment of the CSF in patients with GA to better define the humoral response contributing to disease pathophysiology. In this observational study we assessed the presence of plasma cells in the CSF of 20 patients with GA and 6 controls. CSF from 16 of the GA patients and from all 6 controls was investigated for the presence of anti-TG6 IgA antibodies. Immunohistochemistry for CD138 was performed to assess the presence of plasma cells in the cerebellum and spinal cord of 4 cases with GA, 4 ataxia controls and 4 neurologically healthy controls. A significant increase in anti-TG6 IgA antibodies was detected in the CSF of patients with GA compared to controls, with no correlation between CSF and serum levels of anti-TG6 IgA antibodies for either experimental group. CD138 + cells were present in the CSF of 2 patients with GA and in the cerebellum and spinal cord of 3 post-mortem cases of GA. In a subpopulation of patients with GA intrathecal presence of plasma cells and TG6 antibodies is a feature of the disease, likely associated with prolonged disease duration and continuous exposure to gluten.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Lionfish (Pterois volitans) do not show directional preferences for ambient underwater soundscapes during diurnal hours - Roxanne B Holmes; Nadia M. Hamilton; Stephen D. Simpson; James E. Herbert-Read (Marine Biology, 2025)
Sound is a valuable cue in the marine environment that can inform animals about habitat location and community composition. Indeed, sound is often used for orientation and navigation by larval reef fishes during settlement. However, despite sound’s role in the early life of reef fishes, whether post-settlement reef fishes use ambient soundscapes to inform their movement decisions remains less clear. In an in-situ playback experiment in Curaçao, the Dutch Caribbean, settled individuals of an invasive predator, the Indo-Pacific lionfish ( Pterois volitans ), showed no preference to move towards the playbacks of two different habitat types during daylight hours. In particular, lionfish did not prefer to move towards the sounds of sandy or reef habitat playbacks when tested against a silent control. Moreover, when given a choice between simultaneous sandy and reef habitat playbacks, lionfish showed no preference for the soundscape of either habitat type. While the activity of lionfish was strongly correlated with their body size, with larger fish being more active, activity was not affected by habitat playback, nor did body size affect their preference for the soundscapes of either habitat type. While acoustic lures have been speculated to be a promising addition to existing lionfish trap designs, daytime playbacks of ambient soundscapes are unlikely to be successful in attracting lionfish post-settlement, ultimately affecting their efficacy.

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Ice-marginal volcanic sequence in Iceland found on a nondescript gradual hillslope: An unexpected record of ice thickness late in deglaciation - Audrey R. Putnam; Kirsten L. Siebach; Candice C. Bedford; Sarah L. Simpson; Michael T. Thorpe; Joseph J. Tamborski; Elizabeth B. Rampe (Journal of Volcanology and Geothermal Research, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Response of Root Respiration to Warming and Nitrogen Addition Depends on Tree Species - T. J. Muratore; M. A. Knorr; M. J. Simpson; R. B. Stephens; R. P. Phillips; S. D. Frey (Global Change Biology, 2024)
Roots contribute a large fraction of CO 2 efflux from soils, yet the extent to which global change factors affect root‐derived fluxes is poorly understood. We investigated how red maple ( Acer rubrum ) and red oak ( Quercus rubra ) root biomass and respiration respond to long‐term (15 years) soil warming, nitrogen addition, or their combination in a temperate forest. We found that ecosystem root respiration was decreased by 40% under both single‐factor treatments (nitrogen addition or warming) but not under their combination (heated × nitrogen). This response was driven by the reduction of mass‐specific root respiration under warming and a reduction in maple root biomass in both single‐factor treatments. Mass‐specific root respiration rates for both species acclimated to soil warming, resulting in a 43% reduction, but were not affected by N addition or the combined heated × N treatment. Notably, the addition of nitrogen to warmed soils alleviated thermal acclimation and returned mass‐specific respiration rates to control levels. Oak roots contributed disproportionately to ecosystem root respiration despite the decrease in respiration rates as their biomass was maintained or enhanced under warming and nitrogen addition. In contrast, maple root respiration rates were consistently higher than oak, and this difference became critical in the heated × nitrogen treatment, where maple root biomass increased, contributing significantly more CO 2 relative to single‐factor treatments. Our findings highlight the importance of accounting for the root component of respiration when assessing soil carbon loss in response to global change and demonstrate that combining warming and N addition produces effects that cannot be predicted by studying these factors in isolation.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Association of physical function with connectivity in the sensorimotor and dorsal attention networks: why examining specific components of physical function matters - Madeline C. Boyd; Jonathan H. Burdette; Michael E. Miller; Robert G. Lyday; Christina E. Hugenschmidt; W. Jack Rejeski; Sean L. Simpson; Laura D. Baker; Chal E. Tomlinson; Stephen B. Kritchevsky; Paul J. Laurienti (GeroScience, 2024)
Declining physical function with aging is associated with structural and functional brain network organization. Gaining a greater understanding of network associations may be useful for targeting interventions that are designed to slow or prevent such decline. Our previous work demonstrated that the Short Physical Performance Battery (eSPPB) score and body mass index (BMI) exhibited a statistical interaction in their associations with connectivity in the sensorimotor cortex (SMN) and the dorsal attention network (DAN). The current study examined if components of the eSPPB have unique associations with these brain networks. Functional magnetic resonance imaging was performed on 192 participants in the BNET study, a longitudinal and observational trial of community-dwelling adults aged 70 or older. Functional brain networks were generated for resting state and during a motor imagery task. Regression analyses were performed between eSPPB component scores (gait speed, complex gait speed, static balance, and lower extremity strength) and BMI with SMN and DAN connectivity. Gait speed, complex gait speed, and lower extremity strength significantly interacted with BMI in their association with SMN at rest. Gait speed and complex gait speed were interacted with BMI in the DAN at rest while complex gait speed, static balance, and lower extremity strength interacted with BMI in the DAN during motor imagery. Results demonstrate that different components of physical function, such as balance or gait speed and BMI, are associated with unique aspects of brain network organization. Gaining a greater mechanistic understanding of the associations between low physical function, body mass, and brain physiology may lead to the development of treatments that not only target specific physical function limitations but also specific brain networks.

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

Contractile vacuoles: a rapidly expanding (and occasionally diminishing?) understanding - Kiran J. More; Harpreet Kaur; Alastair G.B. Simpson; Frederick W. Spiegel; Joel B. Dacks (European Journal of Protistology, 2024)

Testing the reproducibility of in situ Lu Hf dating using Lu-rich garnet from the Tørdal pegmatites, southern Norway - Stijn Glorie; Alexander Simpson; Sarah E. Gilbert; Martin Hand; Axel B. Müller (Chemical Geology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Predicting potential spawning areas of European bass, Dicentrarchus labrax, in the Irish and Celtic seas - H. Lincoln; P.E. Robins; S-B. Wilmes; S. Pérez-Mayol; A. Moore; S. Simpson; A. Goward-Brown; C. Heney; S. Malham; B. Morales-Nin; N. Hold; I.D. McCarthy (Fisheries Research, 2024)

An observational and warning system for the aquaculture sector - Diego Pereiro; Oleg Belyaev; Martha B. Dunbar; Andrew Conway; Tomasz Dabrowski; Inger Graves; Gabriel Navarro; Glenn Nolan; Jay Pearlman; Pauline Simpson; Caroline Cusack (Frontiers in Marine Science, 2024)
This work presents the steps followed in the design and implementation of a marine observatory that provides the current state and forecast of oceanic conditions relevant to the aquaculture sector. Examples of successful implementation of these guidelines are presented in the framework of the EuroSea project (H2020 grant agreement No. 862626) for two aquaculture sites: Deenish Island in Ireland and El Campello in Spain. In-situ essential ocean measurements, remote-sensing observations and modelled forecasts are jointly provided to the aquaculture end users. The process begins with stakeholder interaction to understand their main needs and concerns, followed by software architecture design and development to facilitate data acquisition, post-processing and visualization on an open-access web platform. User input regarding the development of the observatory and web platform content and frequent feedback are of paramount importance during the whole process to ensure that the services offered match the needs of the aquaculture sector.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Integrating fecal isotopes and molecular scatology to non-invasively study the spatial ecology of elusive carnivorans: a case study with wild jaguars (Panthera onca) - Brooke E. Crowley; Claudia Wultsch; Emily M. B. Simpson; Marcella J. Kelly (European Journal of Wildlife Research, 2023)

Transcriptomic Profiling Reveals Discrete Poststroke Dementia Neuronal and Gliovascular Signatures - Rachel Waller; Yoshiki Hase; Julie E. Simpson; Paul R. Heath; Matthew Wyles; Rajesh N. Kalaria; Stephen B. Wharton (Translational Stroke Research, 2023)
Poststroke dementia (PSD) is associated with pathology in frontal brain regions, in particular dorsolateral prefrontal cortex (DLPFC) neurons and white matter, remote from the infarct. We hypothesised that PSD results from progressive DLPFC neuronal damage, associated with frontal white matter gliovascular unit (GVU) alterations. We investigated the transcriptomic profile of the neurons and white matter GVU cells previously implicated in pathology. Laser-capture microdissected neurons, astrocytes and endothelial cells were obtained from the Cognitive Function After Stroke cohort of control, PSD and poststroke non-dementia (PSND) human subjects. Gene expression was assessed using microarrays and pathway analysis to compare changes in PSD with controls and PSND. Neuronal findings were validated using NanoString technology and compared with those in the bilateral common carotid artery stenosis (BCAS) mouse model. Comparing changes in PSD compared to controls with changes in PSND compared to controls identified transcriptomic changes associated specifically with dementia. DLPFC neurons showed defects in energy production (tricarboxylic acid (TCA) cycle, adenosine triphosphate (ATP) binding and mitochondria), signalling and communication (MAPK signalling, Toll-like receptor signalling, endocytosis). Similar changes were identified in neurons isolated from BCAS mice. Neuronal findings accompanied by altered astrocyte communication and endothelium immune changes in the frontal white matter, suggesting GVU dysfunction. We propose a pathogenic model in PSD whereby neuronal changes are associated with frontal white matter GVU dysfunction leading to astrocyte failure in supporting neuronal circuits resulting in delayed cognitive decline associated with PSD. Therefore, targeting these processes could potentially ameliorate the dementia seen in PSD.

Usability of existing global and national data for flood related vulnerability assessment in Indonesia - Breanne K. Langlois; Elizabeth Marsh; Tyler Stotland; Ryan B. Simpson; Katherine Berry; David A. Carroll; Aris Ismanto; Magaly Koch; Elena N. Naumova (Science of The Total Environment, 2023)

The impact of leg position on muscle blood flow and oxygenation during low-intensity rhythmic plantarflexion exercise - Kyohei Marume; Hendrik Mugele; Ryo Ueno; Sachin B. Amin; Heru Syarli Lesmana; Carmen Possnig; Alexander B. Hansen; Lydia L. Simpson; Justin S. Lawley (European Journal of Applied Physiology, 2023)
Purpose Resistance training (RT) is an effective countermeasure to combat physical deconditioning whereby localized hypoxia within the limb increases metabolic stress eliciting muscle adaptation. The current study sought to examine the influence of gravity on muscle oxygenation (SmO 2 ) alongside vascular hemodynamic responses. Methods In twelve young healthy adults, an ischemic occlusion test and seven minutes of low-intensity rhythmic plantarflexion exercise were used alongside superficial femoral blood flow and calf near-infrared spectroscopy to assess the microvascular vasodilator response, conduit artery flow-mediated dilation, exercise-induced hyperemia, and SmO 2 with the leg positioned above or below the heart in a randomized order. Results The microvascular vasodilator response, assessed by peak blood flow (798 ± 231 mL/min vs. 1348 ± 290 mL/min; p < 0.001) and reperfusion slope 10 s of SmO 2 after cuff deflation (0.75 ± 0.45%.s-1 vs.2.40 ± 0.94%.s-1; p < 0.001), was attenuated with the leg above the heart. This caused a blunted dilatation of the superficial femoral artery (3.0 ± 2.4% vs. 5.2 ± 2.1%; p = 0.008). Meanwhile, blood flow area under the curve was comparable (above the heart: 445 ± 147 mL vs. below the heart: 474 ± 118 mL; p = 0.55) in both leg positions. During rhythmic exercise, the increase in femoral blood flow was lower in the leg up position (above the heart: 201 ± 94% vs. below the heart: 292 ± 114%; p = 0.001) and contributed to a lower SmO 2 (above the heart: 41 ± 18% vs. below the heart 67 ± 5%; p < 0.001). Conclusion Positioning the leg above the heart results in attenuated peak vascular dilator response and exercise-induced hyperemia that coincided with a lower SmO 2 during low-intensity plantarflexion exercise.

Comparing environmental DNA collection methods for sampling community composition on marine infrastructure - Jason B. Alexander; Michael J. Marnane; Justin I. McDonald; Sherralee S. Lukehurst; Travis S. Elsdon; Tiffany Simpson; Shawn Hinz; Michael Bunce; Euan S. Harvey (Estuarine, Coastal and Shelf Science, 2023)

Clinical validation of the Varian Truebeam intra-fraction motion review (IMR) system for prostate treatment guidance - Guneet Kaur; Joerg Lehmann; Peter B. Greer; Jarad Martin; John Simpson (Physical and Engineering Sciences in Medicine, 2023)

Optimization and Scale Up of Spray Dried CPZEN-45 Aerosol Powders for Inhaled Tuberculosis Treatment - Ian E. Stewart; Phillip G. Durham; Jacob M. Sittenauer; Aranza P. Barreda; Grayson W. Stowell; Carmella Moody; Jeffery B. Mecham; Catherine Simpson; Sharon Daily; Sara E. Maloney; Mark D. Williams; Diana Severynse-Stevens; et al. (Pharmaceutical Research, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Webinar and survey on quality management principles within the Australian and New Zealand ACPSEM Workforce - Emily Simpson-Page; Paul Coogan; Tomas Kron; Nicholas Lowther; Rebecca Murray; Christopher Noble; Ian Smith; Rachael Wilks; Scott B. Crowe (Physical and Engineering Sciences in Medicine, 2022)

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

3D printed brachytherapy jig for Reference Air Kerma Rate calibration - Emily Simpson-Page; Lynsey Hamlett; Dominika Lew; Holly Stephens; Rachael Wilks; Tanya Kairn; Scott B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

The quorum‐sensing systems of Vibrio campbellii DS40M4 and BB120 are genetically and functionally distinct - Chelsea A. Simpson; Blake D. Petersen; Nicholas W. Haas; Logan J. Geyman; Aimee H. Lee; Ram Podicheti; Robert Pepin; Laura C. Brown; Douglas B. Rusch; Michael P. Manzella; Kai Papenfort; Julia C. van Kessel (Environmental Microbiology, 2021)
Summary Vibrio campbellii BB120 (previously classified as Vibrio harveyi ) is a fundamental model strain for studying quorum sensing in vibrios. A phylogenetic evaluation of sequenced Vibrio strains in Genbank revealed that BB120 is closely related to the environmental isolate V. campbellii DS40M4. We exploited DS40M4's competence for exogenous DNA uptake to rapidly generate greater than 30 isogenic strains with deletions of genes encoding BB120 quorum‐sensing system homologues. Our results show that the quorum‐sensing circuit of DS40M4 is distinct from BB120 in three ways: (i) DS40M4 does not produce an acyl homoserine lactone autoinducer but encodes an active orphan LuxN receptor, (ii) the quorum regulatory small RNAs (Qrrs) are not solely regulated by autoinducer signalling through the response regulator LuxO and (iii) the DS40M4 quorum‐sensing regulon is much smaller than BB120 (~100 genes vs. ~400 genes, respectively). Using comparative genomics to expand our understanding of quorum‐sensing circuit diversity, we observe that conservation of LuxM/LuxN proteins differs widely both between and within Vibrio species. These strains are also phenotypically distinct: DS40M4 exhibits stronger interbacterial cell killing, whereas BB120 forms more robust biofilms and is bioluminescent. These results underscore the need to examine wild isolates for a broader view of bacterial diversity in the marine ecosystem.

The Human Element of Restoration Success: Manager Characteristics Affect Vegetation Recovery Following Invasive Tamarix Control - Anna A. Sher; Lisa Clark; Annie L. Henry; Alexander R. B. Goetz; Eduardo González; Anit Tyagi; Isabelle Simpson; Bérenger Bourgeois (Wetlands, 2020)

Correction to: Factors Influencing Carbon Stocks and Accumulation Rates in Eelgrass Meadows Across New England, USA - A. B. Novak; M. C. Pelletier; P. Colarusso; J. Simpson; M. N. Gutierrez; A. Arias-Ortiz; M. Charpentier; P. Masque; P. Vella (Estuaries and Coasts, 2020)

Factors Influencing Carbon Stocks and Accumulation Rates in Eelgrass Meadows Across New England, USA - A. B. Novak; M. C. Pelletier; P. Colarusso; J. Simpson; M. N. Gutierrez; A. Arias-Ortiz; M. Charpentier; P. Masque; P. Vella (Estuaries and Coasts, 2020)
Increasing the protection of coastal vegetated ecosystems has been suggested as one strategy to compensate for increasing carbon dioxide (CO 2 ) in the atmosphere as the capacity of these habitats to sequester and store carbon exceeds that of terrestrial habitats. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems and have an exceptional ability to sequester and store large quantities of carbon in biomass and, particularly, in sediments. However, carbon stocks (C org stocks) and carbon accumulation rates (C org accumulation) in seagrass meadows are highly variable both spatially and temporally, making it difficult to extrapolate this strategy to areas where information is lacking. In this study, C org stocks and C org accumulation were determined at 11 eelgrass meadows across New England, representing a range of eutrophication and exposure conditions. In addition, the environmental factors and structural characteristics of meadows related to variation in C org stocks were identified. The objectives were accomplished by assessing stable isotopes of δ 13 C and δ 15 N as well as %C and %N in plant tissues and sediments, measuring grain size and 210 Pb of sediment cores, and through assessing site exposure. Variability in C org stocks in seagrass meadows is well predicted using commonly measured environmental variables such as grain size distribution. This study allows incorporation of data and insights for the northwest Atlantic, where few studies on carbon sequestration by seagrasses have been conducted.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Development of fly tolerance to consuming a high-protein diet requires physiological, metabolic and transcriptional changes - Ihor S. Yurkevych; Lindsey J. Gray; Dmytro V. Gospodaryov; Nadia I. Burdylyuk; Kenneth B. Storey; Stephen J. Simpson; Oleh Lushchak (Biogerontology, 2020)

Clifford Charles Townsend (1926 – 2018) - B. Townsend; P. J. Cribb; D. A. Simpson (Kew Bulletin, 2020)

Cerebrospinal Fluid Ceruloplasmin, Haptoglobin, and Vascular Endothelial Growth Factor Are Associated with Neurocognitive Impairment in Adults with HIV Infection - A. R. Kallianpur; H. Gittleman; S. Letendre; R. Ellis; J. S. Barnholtz-Sloan; W. S. Bush; R. Heaton; D. C. Samuels; D. R. Franklin; D. Rosario-Cookson; D. B. Clifford; A. C. Collier; et al. (Molecular Neurobiology, 2019)

Genome-wide scans of myopia in Pennsylvania Amish families reveal significant linkage to 12q15, 8q21.3 and 5p15.33 - Anthony M. Musolf; Claire L. Simpson; Theresa A. Alexander; Laura Portas; Federico Murgia; Elise B. Ciner; Dwight Stambolian; Joan E. Bailey-Wilson (Human Genetics, 2019)

White matter damage, neuroinflammation, and neuronal integrity in HAND - Aljoharah Alakkas; Ronald J. Ellis; Caitlin Wei-Ming Watson; Anya Umlauf; Robert K. Heaton; Scott Letendre; Ann Collier; Christina Marra; David B. Clifford; Benjamin Gelman; Ned Sacktor; Susan Morgello; et al. (Journal of NeuroVirology, 2019)

Using meta‐omics of contaminated sediments to monitor changes in pathways relevant to climate regulation - Simone C. Birrer; Katherine A. Dafforn; Melanie Y. Sun; Rohan B. H. Williams; Jaimie Potts; Peter Scanes; Brendan P. Kelaher; Stuart L. Simpson; Staffan Kjelleberg; Sanjay Swarup; Peter Steinberg; Emma L. Johnston (Environmental Microbiology, 2019)
Summary Microbially mediated biogeochemical processes are crucial for climate regulation and may be disrupted by anthropogenic contaminants. To better manage contaminants, we need tools that make real‐time causal links between stressors and altered microbial functions, and the potential consequences for ecosystem services such as climate regulation. In a manipulative field experiment, we used metatranscriptomics to investigate the impact of excess organic enrichment and metal contamination on the gene expression of nitrogen and sulfur metabolisms in coastal sediments. Our gene expression data suggest that excess organic enrichment results in (i) higher transcript levels of genes involved in the production of toxic ammonia and hydrogen sulfide and (ii) lower transcript levels associated with the degradation of a greenhouse gas (nitrous oxide). However, metal contamination did not have any significant impact on gene expression. We reveal the genetic mechanisms that may lead to altered productivity and greenhouse gas production in coastal sediments due to anthropogenic contaminants. Our data highlight the applicability of metatranscriptomics as a management tool that provides an immense breadth of information and can identify potentially impacted process measurements that need further investigation.

Changes in nutritional values induced by butachlor in juvenile diploid and triploid Clarias gariepinus - A. Karami; S. Karbalaei; M. Ebrahimi; A. Ismail; M. F. Jahromi; S. L. Simpson; P. Eghtesadi Araghi; R. P. Lim; J. B. Liang (International Journal of Environmental Science and Technology, 2018)

Ozone pollution will compromise efforts to increase global wheat production - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Malin Broberg; Johan Uddling; Fernando Jaramillo; William J Davies; Frank Dentener; Maurits Van den Berg; Madhoolika Agrawal; Shahibhushan B. Agrawal; et al. (Global Change Biology, 2018)
Introduction of high‐performing crop cultivars and crop/soil water management practices that increase the stomatal uptake of carbon dioxide and photosynthesis will be instrumental in realizing the United Nations Sustainable Development Goal ( SDG ) of achieving food security. To date, however, global assessments of how to increase crop yield have failed to consider the negative effects of tropospheric ozone, a gaseous pollutant that enters the leaf stomatal pores of plants along with carbon dioxide, and is increasing in concentration globally, particularly in rapidly developing countries. Earlier studies have simply estimated that the largest effects are in the areas with the highest ozone concentrations. Using a modelling method that accounts for the effects of soil moisture deficit and meteorological factors on the stomatal uptake of ozone, we show for the first time that ozone impacts on wheat yield are particularly large in humid rain‐fed and irrigated areas of major wheat‐producing countries (e.g. United States, France, India, China and Russia). Averaged over 2010–2012, we estimate that ozone reduces wheat yields by a mean 9.9% in the northern hemisphere and 6.2% in the southern hemisphere, corresponding to some 85 Tg (million tonnes) of lost grain. Total production losses in developing countries receiving Official Development Assistance are 50% higher than those in developed countries, potentially reducing the possibility of achieving UN SDG 2. Crucially, our analysis shows that ozone could reduce the potential yield benefits of increasing irrigation usage in response to climate change because added irrigation increases the uptake and subsequent negative effects of the pollutant. We show that mitigation of air pollution in a changing climate could play a vital role in achieving the above‐mentioned UN SDG , while also contributing to other SDG s related to human health and well‐being, ecosystems and climate change.

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Evaluating the accuracy of self-report for the diagnosis of HIV-associated neurocognitive disorder (HAND): defining “symptomatic” versus “asymptomatic” HAND - Lisa C. Obermeit; Jessica Beltran; Kaitlin B. Casaletto; Donald R. Franklin; Scott Letendre; Ronald Ellis; Christine Fennema-Notestine; Florin Vaida; Ann C. Collier; Christina M. Marra; David Clifford; Benjamin Gelman; et al. (Journal of NeuroVirology, 2017)

Duration of fascicle shortening is affected by muscle architecture and sex - C. L. Simpson; S. Arefin; R. R. Smart; B. Harwood; Jennifer M. Jakobi (European Journal of Applied Physiology, 2016)

Apolipoprotein E ε4 genotype status is not associated with neuroimaging outcomes in a large cohort of HIV+ individuals - Sarah A. Cooley; Robert H. Paul; Christine Fennema-Notestine; Erin E. Morgan; Florin Vaida; Qianqian Deng; Jie Ashley Chen; Scott Letendre; Ronald Ellis; David B. Clifford; Christina M. Marra; Ann C. Collier; et al. (Journal of NeuroVirology, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

Long-term efavirenz use is associated with worse neurocognitive functioning in HIV-infected patients - Qing Ma; Florin Vaida; Jenna Wong; Chelsea A. Sanders; Yu-ting Kao; David Croteau; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; Justin C. McArthur; Susan Morgello; et al. (Journal of NeuroVirology, 2016)

CSF biomarkers of monocyte activation and chemotaxis correlate with magnetic resonance spectroscopy metabolites during chronic HIV disease - Albert M. Anderson; Christine Fennema-Notestine; Anya Umlauf; Michael J. Taylor; David B. Clifford; Christina M. Marra; Ann C. Collier; Benjamin B. Gelman; Justin C. McArthur; J. Allen McCutchan; David M. Simpson; Susan Morgello; et al. (Journal of NeuroVirology, 2015)

Long‐term changes in organic matter and mercury transport to lakes in the sporadic discontinuous permafrost zone related to peat subsidence - Jennifer B. Korosi; Jamylynn McDonald; Kristen A. Coleman; Michael J. Palmer; John P. Smol; Myrna J. Simpson; Jules M. Blais (Limnology and Oceanography, 2015)
Permafrost‐supported peatlands near the southern limit of permafrost are experiencing dramatic landscape changes as a result of recent climate warming, which have the potential to impact aquatic ecosystems through changes in terrestrial run‐off. Our objectives were to determine how terrestrial organic matter inputs to aquatic ecosystems in the southern Northwest Territories (Canada) changed as a result of peat subsidence, and whether terrestrial organic matter can be linked to sedimentary mercury. To accomplish this, we analyzed lipid biomarkers, lignin‐derived phenols, and other geochemical proxies in sediment cores from two lakes (KAK‐1 and TAH‐7) affected by recent peat subsidence. Both lakes experienced substantial shifts in organic matter proxies through time, but the trajectory of change differed, reflecting local heterogeneity in hydrological setting and other environmental factors. In KAK‐1, recent peat subsidence corresponded to a decrease in lignin‐derived phenol yield, increased inferred lignin oxidation, and δ 15 N depletion. In TAH‐7, peat subsidence was likely initiated by a local forest fire, and resulted in an increase in the n ‐alkanol ratio C 30 /(C 30 + C 28 ) (consistent with a warmer, wetter climate), lignin‐derived phenol yield (mainly syringyls), and δ 13 C depletion. In TAH‐7, total mercury inputs were positively correlated to terrestrial carbon inputs, suggesting allochthonous carbon is an important vector for mercury transport to the lake. In both lakes, an increase in the C 23 /(C 23 + C 29 ) n ‐alkane ratio was observed and suggests increased organic matter input from Sphagnum mosses. Our results demonstrate how terrestrial landscape changes occurring as a result of peat subsidence can influence carbon accumulation in aquatic ecosystems in discontinuous permafrost zones.

Cristobalite in the 2011–2012 Cordón Caulle eruption (Chile) - C. Ian Schipper; Jonathan M. Castro; Hugh Tuffen; Fabian B. Wadsworth; Debra Chappell; Andres E. Pantoja; Mark P. Simpson; Eric C. Le Ru (Bulletin of Volcanology, 2015)

Variation in toxicity of a current-use insecticide among resurrected Daphnia pulicaria genotypes - Adam M. Simpson; Punidan D. Jeyasingh; Jason B. Belden (Ecotoxicology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Brain morphometric correlates of metabolic variables in HIV: the CHARTER study - S. L. Archibald; J. A. McCutchan; C. Sanders; T. Wolfson; T. L. Jernigan; R. J. Ellis; B. M. Ances; A. C. Collier; J. C. McArthur; S. Morgello; D. M. Simpson; C. Marra; et al. (Journal of NeuroVirology, 2014)

Separate and combined effects of 21-day bed rest and hypoxic confinement on body composition - Tadej Debevec; Tarsi C. Bali; Elizabeth J. Simpson; Ian A. Macdonald; Ola Eiken; Igor B. Mekjavic (European Journal of Applied Physiology, 2014)

Predicted responses of arctic and alpine ecosystems to altered seasonality under climate change - Jessica G Ernakovich; Kelly A. Hopping; Aaron B. Berdanier; Rodney T. Simpson; Emily J. Kachergis; Heidi Steltzer; Matthew D. Wallenstein (Global Change Biology, 2014)
Global climate change is already having significant impacts on arctic and alpine ecosystems, and ongoing increases in temperature and altered precipitation patterns will affect the strong seasonal patterns that characterize these temperature‐limited systems. The length of the potential growing season in these tundra environments is increasing due to warmer temperatures and earlier spring snow melt. Here, we compare current and projected climate and ecological data from 20 Northern Hemisphere sites to identify how seasonal changes in the physical environment due to climate change will alter the seasonality of arctic and alpine ecosystems. We find that although arctic and alpine ecosystems appear similar under historical climate conditions, climate change will lead to divergent responses, particularly in the spring and fall shoulder seasons. As seasonality changes in the Arctic, plants will advance the timing of spring phenological events, which could increase plant nutrient uptake, production, and ecosystem carbon (C) gain. In alpine regions, photoperiod will constrain spring plant phenology, limiting the extent to which the growing season can lengthen, especially if decreased water availability from earlier snow melt and warmer summer temperatures lead to earlier senescence. The result could be a shorter growing season with decreased production and increased nutrient loss. These contrasting alpine and arctic ecosystem responses will have cascading effects on ecosystems, affecting community structure, biotic interactions, and biogeochemistry.

Investigation of insecticide leaching from potted nursery stock and aquatic health benefits of bioretention cells receiving nursery runoff - Grant M. Graves; Jason R. Vogel; Jason B. Belden; Eric J. Rebek; Adam M. Simpson (Environmental Science and Pollution Research, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Detecting Extinction Risk from Climate Change by IUCN Red List Criteria - DAVID A. KEITH; MICHAEL MAHONY; HARRY HINES; JANE ELITH; TRACEY J. REGAN; JOHN B. BAUMGARTNER; DAVID HUNTER; GEOFFREY W. HEARD; NICOLA J. MITCHELL; KIRSTEN M. PARRIS; TRENT PENMAN; BEN SCHEELE; et al. (Conservation Biology, 2014)
Anthropogenic climate change is a key threat to global biodiversity. To inform strategic actions aimed at conserving biodiversity as climate changes, conservation planners need early warning of the risks faced by different species. The IUCN Red List criteria for threatened species are widely acknowledged as useful risk assessment tools for informing conservation under constraints imposed by limited data. However, doubts have been expressed about the ability of the criteria to detect risks imposed by potentially slow‐acting threats such as climate change, particularly because criteria addressing rates of population decline are assessed over time scales as short as 10 years. We used spatially explicit stochastic population models and dynamic species distribution models projected to future climates to determine how long before extinction a species would become eligible for listing as threatened based on the IUCN Red List criteria. We focused on a short‐lived frog species (Assa darlingtoni) chosen specifically to represent potential weaknesses in the criteria to allow detailed consideration of the analytical issues and to develop an approach for wider application. The criteria were more sensitive to climate change than previously anticipated; lead times between initial listing in a threatened category and predicted extinction varied from 40 to 80 years, depending on data availability. We attributed this sensitivity primarily to the ensemble properties of the criteria that assess contrasting symptoms of extinction risk. Nevertheless, we recommend the robustness of the criteria warrants further investigation across species with contrasting life histories and patterns of decline. The adequacy of these lead times for early warning depends on practicalities of environmental policy and management, bureaucratic or political inertia, and the anticipated species response times to management actions. Detección del Riesgo de Extinción a partir del Cambio Climático por medio del Criterio de la Lista Roja de la UICNKeith et al.

What Toxicity May Result from Ingestion of the Plant Pictured Below? Answer: Cardioactive Steroid Toxicity from Common Milkweed - Nicholas S. Simpson; Jon B. Cole; Heather Ellsworth (Journal of Medical Toxicology, 2013)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Erratum to: Adaptive feedback analysis and control of programmable stimuli for assessment of cerebrovascular function - Lingke Fan; Glen Bush; Emmanuel Katsogridakis; David M. Simpson; Robert Allen; John Potter; Anthony A. Birch; Ronney B. Panerai (Medical & Biological Engineering & Computing, 2013)

Adaptive feedback analysis and control of programmable stimuli for assessment of cerebrovascular function - Lingke Fan; Glen Bush; Emmanuel Katsogridakis; David M. Simpson; Robert Allen; John Potter; Anthony A. Birch; Ronney B. Panerai (Medical & Biological Engineering & Computing, 2013)

Apolipoprotein E4 genotype does not increase risk of HIV-associated neurocognitive disorders - E. E. Morgan; S. P. Woods; S. L. Letendre; D. R. Franklin; C. Bloss; A. Goate; R. K. Heaton; A. C. Collier; C. M. Marra; B. B. Gelman; J. C. McArthur; S. Morgello; et al. (Journal of NeuroVirology, 2013)

Considerations for modeling burn probability across landscapes with steep environmental gradients: an example from the Columbia Mountains, Canada - Marc-André Parisien; Gregg R. Walker; John M. Little; Brian N. Simpson; Xianli Wang; Daniel D. B. Perrakis (Natural Hazards, 2013)

‘Diatoms and pH reconstruction’ (1990) revisited - H. John B. Birks; Gavin L. Simpson (Journal of Paleolimnology, 2013)

The Benefits of Spatially Targeted Water Level Management for Salinity Reduction in a Coastal Aquifer - I. P. Holman; K. R. Rushton; T. B. Simpson (Water Resources Management, 2013)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

A microsatellite linkage map for the cultivated strawberry (Fragaria × ananassa) suggests extensive regions of homozygosity in the genome that may have resulted from breeding and selection - D. J. Sargent; T. Passey; N. Šurbanovski; E. Lopez Girona; P. Kuchta; J. Davik; R. Harrison; A. Passey; A. B. Whitehouse; D. W. Simpson (Theoretical and Applied Genetics, 2012)

Transgenic Stra8-EYFP pigs: a model for developing male germ cell technologies - Jeffrey R. Sommer; Lauren R. Jackson; Sean G. Simpson; Edwin B. Collins; Jorge A. Piedrahita; Robert M. Petters (Transgenic Research, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

Monitoring changes in physical performance with heart rate measures in young soccer players - M. Buchheit; M. B. Simpson; H. Al Haddad; P. C. Bourdon; A. Mendez-Villanueva (European Journal of Applied Physiology, 2012)

Consequences of frugivore‐mediated seed dispersal for the spatial and genetic structures of a neotropical palm - J. CHOO; T. E. JUENGER; B. B. SIMPSON (Molecular Ecology, 2012)
The idiosyncratic behaviours of seed dispersers are important contributors to plant spatial associations and genetic structures. In this study, we used a combination of field, molecular and spatial studies to examine the connections between seed dispersal and the spatial and genetic structures of a dominant neotropical palm Attalea phalerata. Field observation and genetic parentage analysis both indicated that the majority of A. phalerata seeds were dispersed locally over short distances ( 10 m) from maternal palms. Seedlings were also spatially aggregated with juveniles. These patterns are probably associated with the dispersal of seeds by rodents and the survival of recruits at specific microsites or neighbourhoods over successive fruiting periods. Our cross‐cohort analyses found palms in older cohorts and cohort pairs were associated with a lower proportion of offspring and sibling neighbours and exhibited weaker spatial and genetic structures. Such patterns are consistent with increased distance‐ and density‐dependent mortality over time among palms dispersed near maternal palms or siblings. The integrative approaches used for this study allowed us to infer the importance of seed dispersal activities in maintaining the aggregated distribution and significant genetic structures among A. phalerata palms. We further conclude that distance‐ and density‐dependent mortality is a key postdispersal process regulating this palm population.

Internal seiche modes and bottom boundary‐layer dissipation in a temperate lake from acoustic measurements - J. H. Simpson; P. J. Wiles; B. J. Lincoln (Limnology and Oceanography, 2011)
Measurements with Acoustic Doppler Current Profilers (ADCPs) and a thermistor string were used to investigate the seasonal variation of internal seiches in a 5‐km‐long temperate lake and the dissipation induced by the seiches in the bottom boundary layer. Velocity data, from a bottom‐mounted 1.2‐MHz ADCP were analyzed by cross‐spectral analysis to determine the seiche modes. The first vertical mode was generally dominant but the second mode made a significant contribution at times and was present throughout the summer season. The modal periods, which were consistent with normal mode analysis, exhibited a marked seasonal change that correlated closely with the evolution of stratification. Measurements in the bottom boundary layer, by another ADCP, in pulse‐pulse coherent‐mode sampling at 4 Hz, allowed determination of the rate of turbulent kinetic energy dissipation via the Structure Function Method. Episodes of energy dissipation ~ 10 ‐7 W kg ‐1 occurred during peak flow (~ 0.05 m s ‐1 ) in the seiche motion (period ~ 10 h) and coincided with times of significant Reynolds stress. Between these episodes, dissipation fell below the noise level (~ 5 × 10 ‐9 W kg ‐1 ). The ratio of internal wave energy to the boundary‐layer dissipation rate implies a decay time of ~ 75 h, which is similar to that for energy decay in strong seiches, indicating that boundary‐layer dissipation makes a substantial contribution to energy loss from seiche motions. A major mixing event in August caused by near‐resonant wind forcing brought metalimnion water to the surface and induced substantial mixing.

Enzymatic Characterisation of USP7 Deubiquitinating activity and Inhibition - Jonathan D. Wrigley; Kay Eckersley; Ian M. Hardern; Lindsey Millard; Michael Walters; Stephen W. Peters; Richard Mott; Thorsten Nowak; Richard A. Ward; Peter B. Simpson; Kevin Hudson (Cell Biochemistry and Biophysics, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Vegetative reproduction facilitates early expansion of Phyla canescens in a semi-arid floodplain - J. N. Price; M. J. Macdonald; C. L. Gross; R. D. B. Whalley; I. H. Simpson (Biological Invasions, 2011)

Isolation and fractionation of soil humin using alkaline urea and dimethylsulphoxide plus sulphuric acid - Guixue Song; Michael H. B. Hayes; Etelvino H. Novotny; Andre J. Simpson (The Science of Nature, 2011)

A wide diversity of previously undetected free‐living relatives of diplomonads isolated from marine/saline habitats - Martin Kolisko; Jeffrey D. Silberman; Ivan Cepicka; Naoji Yubuki; Kiyotaka Takishita; Akinori Yabuki; Brian S. Leander; Isao Inouye; Yuji Inagaki; Andrew J. Roger; Alastair G. B. Simpson (Environmental Microbiology, 2010)
Summary Over the last 15 years classical culturing and environmental PCR techniques have revealed a modest number of genuinely new major lineages of protists; however, some new groups have greatly influenced our understanding of eukaryote evolution. We used culturing techniques to examine the diversity of free‐living protists that are relatives of diplomonads and retortamonads, a group of evolutionary and parasitological importance. Until recently, a single organism, Carpediemonas membranifera , was the only representative of this region of the tree. We report 18 new isolates of Carpediemonas ‐like organisms (CLOs) from anoxic marine sediments. Only one is a previously cultured species. Eleven isolates are conspecific and were classified within a new genus, Kipferlia n. gen. The remaining isolates include representatives of three other lineages that likely represent additional undescribed genera (at least). Small‐subunit ribosomal RNA gene phylogenies show that CLOs form a cloud of six major clades basal to the diplomonad‐retortamonad grouping (i.e. each of the six CLO clades is potentially as phylogenetically distinct as diplomonads and retortamonads). CLOs will be valuable for tracing the evolution of diplomonad cellular features, for example, their extremely reduced mitochondrial organelles. It is striking that the majority of CLO diversity was undetected by previous light microscopy surveys and environmental PCR studies, even though they inhabit a commonly sampled environment. There is no reason to assume this is a unique situation – it is likely that undersampling at the level of major lineages is still widespread for protists.

Comparison of reproductive development in triploid and diploid female rainbow trout Oncorhynchus mykiss - Y. Han; M. Liu; L. Lan Zhang; B. Simpson; G. Xue Zhang (Journal of Fish Biology, 2010)
The diploid rainbow trout Oncorhynchus mykiss reached sexual maturity 3 years after hatching and its oogenesis underwent four stages, which were oogonia, primary oocyte, secondary oocyte and egg. Reproductive development and hormone changes of 4 to 35 month‐old female O. mykiss were investigated using histological and radioimmunoassay methods in order to provide a theoretical and practical basis for the use of triploid female O. mykiss . The oogonium of the triploid female could develop into the oocytes of the prophase with abortion occurring later; the oogonium was surrounded by stroma cells to form the oogonium cluster and the gonads showed a virilescent tendency when the oogonium clusters were gradually replaced by spermatogenic‐like cytocysts. After 13 months, amounts of gonadotropic hormone (GtH‐I, GtH‐II) and oestradiol (17 β ‐E 2 ) in triploid females were lower than in diploid fish at corresponding time periods, but the amounts of testosterone (T) increased consistently after 21 months and were more than in diploid fish in the corresponding time periods ( P > 0·05). The infertility of triploid females resulted from meiosis failure, which caused developmental abortion of oocytes and oogonium formed cytocysts before the prophase oocytes. The cytocyst formation was due to the lack of the normal interaction of ovum and follicular cells, the development of follicular cells producing steroids were inhibited, the arylate path from T to 17 β ‐E 2 was interrupted, concentration of 17 β ‐E 2 decreased and concentration of T increased in the blood, the content of vitellogenin (Vg) decreased in the liver with a low 17 β ‐E 2 and high T caused to ovaries to show a tendency to be virilescent.

Characterization of halotolerant Bicosoecida and Placididea (Stramenopila) that are distinct from marine forms, and the phylogenetic pattern of salinity preference in heterotrophic stramenopiles - Jong Soo Park; Alastair G. B. Simpson (Environmental Microbiology, 2010)
Summary Recent culture‐based studies demonstrate the distinctiveness of the microbial eukaryote biota of very hypersaline environments. In contrast, microscopy‐based faunistic studies suggest that the biota of habitats of more moderate hypersalinity (60–150‰) overlaps substantially with that of marine environments, but this has barely been studied with modern techniques. To investigate the diversity and salinity tolerance range of these organisms, eight cultures of heterotrophic stramenopiles were established from (or from nearby) moderately hypersaline locations. These isolates represent five independent groups; Groups A, B and C are bicosoecids; Groups D and E belong to Placididea. One isolate (Group A) is a strain of the widespread marine species Cafeteria roenbergensis , and cannot grow above 100‰ salinity. The other isolates – Groups B–E – can all grow at 150–175‰ salinities and are probably moderate halophiles. Groups B–E all represent previously unsequenced species or even genera, although Group B is the sister group of the borderline extreme halophile Halocafeteria. The high level of novelty en countered suggests that moderately hypersaline environments may harbour a heterotrophic stramenopile biota distinct from that of marine environments. Interestingly, our new isolates are all most closely related to marine or halophilic forms, and our phylogenies show large clades defined by saline/non‐saline habitats within bicosoecids, placidomonads and related lineages. In particular, most freshwater/soil bicosoecids form one well‐supported clade. The sole major exception is Bicosoeca , which is intermixed with marine environmental sequences originally referred to as ‘MAST‐13’, which are from brackish water, not typical seawater. It seems that the freshwater/marine barrier has been crossed very few times in the evolutionary history of these heterotrophic stramenopile flagellates.

Loss of functional diversity under land use intensification across multiple taxa - Dan F. B. Flynn; Melanie Gogol‐Prokurat; Theresa Nogeire; Nicole Molinari; Bárbara Trautman Richers; Brenda B. Lin; Nicholas Simpson; Margaret M. Mayfield; Fabrice DeClerck (Ecology Letters, 2009)
Land use intensification can greatly reduce species richness and ecosystem functioning. However, species richness determines ecosystem functioning through the diversity and values of traits of species present. Here, we analyze changes in species richness and functional diversity (FD) at varying agricultural land use intensity levels. We test hypotheses of FD responses to land use intensification in plant, bird, and mammal communities using trait data compiled for 1600+ species. To isolate changes in FD from changes in species richness we compare the FD of communities to the null expectations of FD values. In over one‐quarter of the bird and mammal communities impacted by agriculture, declines in FD were steeper than predicted by species number. In plant communities, changes in FD were indistinguishable from changes in species richness. Land use intensification can reduce the functional diversity of animal communities beyond changes in species richness alone, potentially imperiling provisioning of ecosystem services.

A Bayesian palaeoenvironmental transfer function model for acidified lakes - Philip B. Holden; Anson W. Mackay; Gavin L. Simpson (Journal of Paleolimnology, 2008)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

The Role of Cohort Studies in Drug Development: Clinical Evidence of Antiviral Activity of Serotonin Reuptake Inhibitors and HMG-CoA Reductase Inhibitors in the Central Nervous System - Scott L. Letendre; Jennifer Marquie-Beck; Ronald J. Ellis; Steven Paul Woods; Brookie Best; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina Marra; Justin C. McArthur; J. Allen McCutchan; Susan Morgello; et al. (Journal of Neuroimmune Pharmacology, 2007)

Halocafeteria seosinensis gen. et sp. nov. (Bicosoecida), a halophilic bacterivorous nanoflagellate isolated from a solar saltern - Jong S. Park; Byung C. Cho; Alastair G. B. Simpson (Extremophiles, 2006)

Iron and cadmium uptake by duodenum of hypotransferrinaemic mice - Kishor B. Raja; Shahnaz E. Jafri; Timothy J. Peters; Robert J. Simpson (BioMetals, 2006)

An enhanced microsatellite map of diploid Fragaria - D. J. Sargent; J. Clarke; D. W. Simpson; K. R. Tobutt; P. Arús; A. Monfort; S. Vilanova; B. Denoyes-Rothan; M. Rousseau; K. M. Folta; N. V. Bassil; N. H. Battey (Theoretical and Applied Genetics, 2006)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Transcriptional profiling of the hyperthermophilic methanarchaeon Methanococcus jannaschii in response to lethal heat and non‐lethal cold shock - Boonchai B. Boonyaratanakornkit; Anjana J. Simpson; Timothy A. Whitehead; Claire M. Fraser; Najib M. A. El‐Sayed; Douglas S. Clark (Environmental Microbiology, 2005)
Summary Temperature shock of the hyperthermophilic methanarchaeon Methanococcus jannaschii from its optimal growth temperature of 85°C to 65°C and 95°C resulted in different transcriptional responses characteristic of both the direction of shock (heat or cold shock) and whether the shock was lethal. Specific outcomes of lethal heat shock to 95°C included upregulation of genes encoding chaperones, and downregulation of genes encoding subunits of the H + transporting ATP synthase. A gene encoding an α subunit of a putative prefoldin was also upregulated, which may comprise a novel element in the protein processing pathway in M. jannaschii . Very different responses were observed upon cold shock to 65°C. These included upregulation of a gene encoding an RNA helicase and other genes involved in transcription and translation, and upregulation of genes coding for proteases and transport proteins. Also upregulated was a gene that codes for an 18 kDa FKBP‐type PPIase, which may facilitate protein folding at low temperatures. Transcriptional profiling also revealed several hypothetical proteins that respond to temperature stress conditions.

Clinical validation of the NeuroScreen - Ronald J Ellis; Scott R Evans; David B Clifford; Lauren R Moo; Justin C McArthur; Ann C Collier; Constance Benson; Ron Bosch; David Simpson; Constantin T Yiannoutsos; Yijun Yang; Kevin Robertson; et al. (Journal of NeuroVirology, 2005)

The biogeography of Hoffmannseggia (Leguminosae, Caesalpinioideae, Caesalpinieae): a tale of many travels - Beryl B. Simpson; Jennifer A. Tate; Andrea Weeks (Journal of Biogeography, 2005)
Aim The flowering plant genus Hoffmannseggia consists of 21 species distributed amphitropically between the arid regions of the south‐western United States and adjacent Mexico, and west‐central South America. This pattern of geographical disjunction is shared by numerous other angiosperm genera and has been the subject of discussions for more than a century with various authors advocating a northern origin for particular taxa and others advocating a southern origin. This study uses a well‐supported phylogeny of a genus with numerous species in each area to address the issues of a northern or southern origin and the facility with which organisms move between the two continents. Location South‐western United States and northern Mexico, northern Chile and Argentina, southern Bolivia, and western Peru. Methods Using DNA sequence data from the nuclear and chloroplast genomes, we generated a phylogenetic hypothesis for all species of Hoffmannseggia rooted with Zuccagnia and Balsamocarpon. Geographical data were optimized on the resultant tree to assess the probable continent of origin for the genus, the pattern of disjunctions between North and South America, and species radiations within the genus. Main conclusions Hoffmannseggia arose in South America and initially split into a suffrutescent (somewhat woody) and an herbaceous clade. Within each of these major clades, there have been at least two exchanges between North and South America. There are no data to support an ancestral pan‐American range for Hoffmannseggia and we therefore ascribe the amphitropical disjunctions to long‐distance dispersal. The phylogeny clearly shows that all dispersals were from South to North America and they occurred at different times and thus the pattern is not the result of a single simultaneous set of dispersals.

Effects of administration of somatostatin‐14 and immunoneutralization of somatostatin on endocrine and growth responses in rainbow trout - B. C. Peterson; P. R. Simpson; K. D. Cain; R. H. Hardy; G. T. Schelling; T. L. Ott (Journal of Fish Biology, 2003)
Injection of somatostatin‐14 (SS‐14) at 5 ng g −1 body mass (BM) into rainbow trout Oncorhynchus mykiss decreased ( P r 2 = 0·54) levels of growth hormone (GH) (1·5 ± 0·9 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time when compared to controls. Somatostatin‐14 at 50 ng g −1 BM also decreased ( P = 0·064, q uadratic; r 2 = 0·30) levels of GH (3·6 ± 2·1 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time compared to controls. In a second study, passive immunization against SS‐14 (1 : 25 dose) increased ( P = 0·10, cubic, r 2 = 0·12) levels of GH (11·0 ± 4·8 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time. Passively immunizing against SS‐14 (1 : 50 dose) increased ( P r 2 = 0·10) levels of GH (8·2 ± 2·3 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time compared to controls. Overall, in the active immunization study there was no difference ( P > 0·10) in specific growth rate ( G ) or feed conversion ratio ( FCR ) between the three treatment groups during the 9 weeks of the study. Only four of the fish immunized against SS‐14, however, developed antibody titres against SS. Compared to controls, these fish exhibited a G of 0·89 ± 0·09 v. 0·56 ± 0·09% per 3 weeks and FCR of 0·80 ± 0·04 v. 1·20 ± 0·05 g g −1 . In SS‐14 immunized fish, levels of GH decreased ( P P G and FCR is dependent upon generation of antibody titres.

Microphysics, radiation and surface processes in the Goddard Cumulus Ensemble (GCE) model - Wei-Kuo Tao; J. Simpson; D. Baker; S. Braun; M.-D. Chou; B. Ferrier; D. Johnson; A. Khain; S. Lang; B. Lynn; C.-L. Shie; D. Starr; et al. (Meteorology and Atmospheric Physics, 2003)

CSF/peripheral nervous system - B. Brew; D. Simpson (Journal of NeuroVirology, 2002)

CSF/peripheral nervous system - B. Brew; D. Simpson (Journal of NeuroVirology, 2002)

A Parametric Approach to Measuring Cerebral Blood Flow Autoregulation from Spontaneous Variations in Blood Pressure - David M. Simpson; Ronney B. Panerai; David H. Evans; A. Ross Naylor (Annals of Biomedical Engineering, 2001)

Estimating normal and pathological dynamic responses in cerebral blood flow velocity to step changes in end-tidal pCO2 - D. M. Simpson; R. B. Panerai; D. H. Evans; J. Garnham; A. R. Naylor; P. R. F. Bell (Medical & Biological Engineering & Computing, 2000)

Phase relations, singularities and thermobarometry of metamorphic assemblages containing phengite, chlorite, biotite, K-feldspar, quartz and H2O - G. D. H. Simpson; A. B. Thompson; J. A. D. Connolly (Contributions to Mineralogy and Petrology, 2000)

Objective Response Detection in an Electroencephalogram During Somatosensory Stimulation - David M. Simpson; Carlos J. Tierra-Criollo; Renato T. Leite; Eduardo J. B. Zayen; Antonio F. C. Infantosi (Annals of Biomedical Engineering, 2000)

Centrin in the groove: immunolocalisation of centrin and microtubules in the putatively primitive protistChilomastix cuspidata (Retortamonadida) - N. D. Weerakoon; J. D. I. Harper; A. G. B. Simpson; D. J. Patterson (Protoplasma, 1999)

The ferric-reducing activity of duodenal brush-border membrane vesicles is associated with a b-type haem - David J. Pountney; Kishor B. Raja; Robert J. Simpson<; John M. Wrigglesworth (BioMetals, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

On the role of ?hot towers? in tropical cyclone formation - J. Simpson; J. B. Halverson; B. S. Ferrier; W. A. Petersen; R. H. Simpson; R. Blakeslee; S. L. Durden (Meteorology and Atmospheric Physics, 1998)

The circumscription ofHoffmannseggia (Fabaceae, Caesalpinioideae, Caesalpinieae) and its allies using morphological and cpDNA restriction site data - Beryl B. Simpson; Bo-Mao Miao (Plant Systematics and Evolution, 1997)

Announcement - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Erratum - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Uptake of 26-Al and 67-Ga into brain and other tissues of normal and hypotransferrinaemic mice - Aleksandar Radunovic´; Fukiko Ueda; Kishor B. Raja; Robert J. Simpson; Jill Templar; Samantha J. King; John S. Lilley; J. Philip Day; Michael W.B. Bradbury (BioMetals, 1997)

Moxonidine and cognitive function: interactions with moclobemide and lorazepam - K. Wesnes; P. M. Simpson; B. Jansson; A. Grahnén; H.-J. Weimann; H. Küppers (European Journal of Clinical Pharmacology, 1997)

Hydrogen-stimulated CO2 fixation and coordinate induction of hydrogenase and ribulosebiphosphate carboxylase in a H2-uptake positive strain of Rhizobium japonicum - Frank B. Simpson; Robert J. Maier; Harold J. Evans (Archives of Microbiology, 1979)

A comparative study of O'nyong nyong virus with Chikungunya virus and plaque variants - A. C. Chanas; Z. Hubalek; B. K. Johnson; D. I. H. Simpson (Archives of Virology, 1979)